The development of a strategy for integrated manufacturing systems a concise guide for the senior executive (Institution of Production Engineers, 1990)
The book covers the following topics relating to integrated manufacturing systems. Three such topics that arose immediately were: 1) a strategic approach 2) the organisational implications and 3) hardware and software communications.